2001
DOI: 10.1037/0022-3514.81.4.684
|View full text |Cite
|
Sign up to set email alerts
|

Can people feel happy and sad at the same time?

Abstract: The authors investigated whether people can feel happy and sad at the same time. J. A. Russell and J. M. Carroll's (1999) circumplex model holds that happiness and sadness are polar opposites and, thus, mutually exclusive. In contrast, the evaluative space model (J. T. Cacioppo & G. G. Berntson, 1994) proposes that positive and negative affect are separable and that mixed feelings of happiness and sadness can co-occur. The authors both replicated and extended past research by showing that whereas most particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
741
5
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 871 publications
(817 citation statements)
references
References 39 publications
32
741
5
9
Order By: Relevance
“…A correlation near zero suggests that a person experiences positive and negative affect independently; a negative correlation suggests that they are experienced on a single continuum. Related research on mixed emotions demonstrates that people can experience pleasant and unpleasant emotions at the same time (Larsen, McGraw, & Cacioppo, 2001;Larsen & McGraw, 2011).…”
Section: Emodiversity and The Emotional Ecosystemmentioning
confidence: 99%
“…A correlation near zero suggests that a person experiences positive and negative affect independently; a negative correlation suggests that they are experienced on a single continuum. Related research on mixed emotions demonstrates that people can experience pleasant and unpleasant emotions at the same time (Larsen, McGraw, & Cacioppo, 2001;Larsen & McGraw, 2011).…”
Section: Emodiversity and The Emotional Ecosystemmentioning
confidence: 99%
“…Though models of affect in psychology typically conceptualize positive and negative affect as diametric opposites (Larsen & Diener, 1992;Russell & Carroll, 1999;Watson & Tellegen, 1999), a study by Larsen, McGraw, & Cacioppo (2001) found situations where people felt happy and sad simultaneously. Diener & Iran-Nejad (1986) found positive and negative emotions were mutually exclusive at high levels, but they often co-existed at low and moderate levels.…”
Section: Development Of the Research Modelmentioning
confidence: 99%
“…Recent research of Oliver and her colleagues (Oliver, 2008;Oliver, Limparos, Tamul, & Woolley, 2009) has extended the scope of feeling qualities that may account for the appeal of tragic entertainment, highlighting the role of feelings such as tenderness (e.g., tender, kindly, understanding, sympathetic, warm) and meaningful affect (e.g., compassionate, inspired, introspective, and contemplative). Rather than sadness proper, these feelings seem to be characterized by the experience of mixed affect, that is, feeling happy and sad at the same time (cf., Larsen, McGraw, & Cacioppo, 2001).…”
Section: Meta-emotionmentioning
confidence: 99%